COVID-19 drives medical education reform to promote “healthy China 2030” action plan - Han, Liping; Wu, Fuyun (Frontiers in Public Health, 2024)
In June 2019, the Chinese government proposed the Healthy China Action Plan (2019–2030) development strategy, which focuses on disease prevention and health promotion. It is expected that by 2030, the national health literacy level will be significantly improved, premature mortality caused by major chronic diseases will be significantly reduced, the average healthy life expectancy will be greatly improved, and the main health indicators of residents will enter the ranks of high-income countries. Unfortunately, at the end of 2019, COVID-19 began to break out in Wuhan, China, which had a huge impact on China's economy and people's health. A series of problems in China's health care and medical education were exposed in the prevention and treatment of the epidemic. How to reform medical education and build a medical talent training system with Chinese characteristics is the key to achieving China's Health 2030 strategy. This article will explore the direction of medical education reform in China under the background of the “Healthy China 2030” strategy and the post pandemic era.